2020
DOI: 10.1002/ange.201916335
|View full text |Cite
|
Sign up to set email alerts
|

Homonuclear Decoupling in 1H NMR of Solids by Remote Correlation

Abstract: The typical linewidths of 1H NMR spectra of powdered organic solids at 111 kHz magic‐angle spinning (MAS) are of the order of a few hundred Hz. While this is remarkable in comparison to the tens of kHz observed in spectra of static samples, it is still the key limit to the use of 1H in solid‐state NMR, especially for complex systems. Here, we demonstrate a novel strategy to further improve the spectral resolution. We show that the anti‐z‐COSY experiment can be used to reduce the residual line broadening of 1H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Time evolution under such a zeroquantum Hamiltonian does not lead to line splitting, but a line shift has been shown for the rank-one part of the J coupling (Andrew and Farnell, 1968), which also has a purely zero-quantum Hamiltonian (Mehring, 1983). This fact has also been mentioned in a recent paper about homonuclear J decoupling in solids (Moutzouri et al, 2020). As a consequence of this, the second-order Hamiltonian will not only lead to a line broadening, but also a shift of the line that depends on the spinning frequency.…”
Section: mentioning
confidence: 68%
See 1 more Smart Citation
“…Time evolution under such a zeroquantum Hamiltonian does not lead to line splitting, but a line shift has been shown for the rank-one part of the J coupling (Andrew and Farnell, 1968), which also has a purely zero-quantum Hamiltonian (Mehring, 1983). This fact has also been mentioned in a recent paper about homonuclear J decoupling in solids (Moutzouri et al, 2020). As a consequence of this, the second-order Hamiltonian will not only lead to a line broadening, but also a shift of the line that depends on the spinning frequency.…”
Section: mentioning
confidence: 68%
“…Experimental observations of the residual homogeneous line width as a function of spinning frequency show that it can often be approximated by a linear correlation with the inverse of the spinning frequency with some deviation that indicates a partial inverse quadratic dependence (Nishiyama, 2016;Sternberg et al, 2018;Penzel et al, 2019;Schledorn et al, 2020). This has been attributed to third-order contributions to the effective Hamiltonian or to chemical-shift effects (Sternberg et al, 2018;Moutzouri et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the coherence transfer efficiency of the INEPT pulse sequence is significantly improved with the use of 1 H homonuclear decoupling schemes under the fast-MAS conditions . It is also shown that homogeneous 1 H line width can be reduced by an anti-z-COSY experiment, which was introduced initially to suppress multiple homonuclear scalar couplings in solution NMR . In silico narrowed 1 H spectra can be obtained by simultaneously fitting the experimental 1 H line shape at various MAS frequencies and predicting 1 H spectra free of homogeneous broadening …”
Section: Evolution Of Fast Very Fast and Ultrafast Mas Probesmentioning
confidence: 99%
“…The anti-z-cosy experiment was proposed in solution-state NMR to obtain homonuclear decoupled proton spectra, albeit at reduced sensitivity, increased acquisition time, and dimensionality . Emsley and co-workers recently adapted the solution state anti-z-COSY experiments to solids at UFMAS . They observed a factor of 2 narrowing in proton line widths at different MAS frequencies.…”
Section: Other Topicsmentioning
confidence: 99%
See 1 more Smart Citation